Regional brand: the essence and formation model - V. A. Klimenko; E. A. Chudinova; T. I. Bannikova; I. O. Dydykin (Вестник университета)
The most critical resource for development and promotion of Russian regions and cities, along with other strategic management tools, is regional bran ding. Branding effectiveness depends on many conditions, including the depth, consistency and scientific understanding of the brand as a tool of a region’s attractiveness. Using a theoretical analysis of scientific literature, the article explains the concept of “regional brand” in terms of key characteristics definition that reflect the specificity of the term. The results of the study concluded that the development and promotion of a regional brand is a complex process which starts with the formation of an integrated system of brand elements. The analysis of experience in designing of the Russian regions’ own brands and the use of the structural modeling method allowed to present a regional brand formation model, describing the main elements of the brand. In the presented model the following six elements were identified: brand platform, positioning, internal brand power, external brand power, communications, resonance. The correlation of each element in the overall system, their importance and influence on the formation of the image and increase in effectiveness of a region’s promotion were determined. The obtained results may be required by representatives of regional administrations that address the branding of territories issues.